Abstracts on Tropical Agriculture. V.18. (Krips Repro BV : KIT, 1993)
General Information. Subject Index. List of Abstracts. Geographical Index. Plant Taxonomic Name Index. Author Index.
Keywords: Agriculture; Tropical Agriculture